Multireligious Culture for Developing Tolerance Character at Elementary School - Eva Sri Rohani; Muh Natsir; Fita Dewi Yuniar (Ananda: Jurnal Pendidikan Anak dan Remaja, 2026)
The research titled "Multireligious Culture for the Development of Tolerance Character at SD Negeri Kasihan Yogyakarta" is based on the idealism of the school as a safe space that facilitates interfaith interactions. However, the reality shows instances of bullying against Catholic students, the marginalization of Hindu students, and the feeling of being marginalized among non-Muslim teachers due to the lack of multireligious interaction. This condition encourages the school to initiate a multireligious culture as a strategy to strengthen the character of tolerance. This study uses a descriptive qualitative approach to describe the implementation of a multireligious culture, the profile of the school's tolerance character, and its contribution to the development of student tolerance. Data were collected thru observation, documentation, and in-depth interviews with informants selected thru purposive sampling, including the principal, teachers, and students of Islamic, Catholic, and Hindu faiths. Data analysis was conducted thru reduction, presentation, and conclusion drawing, with validity testing using source and technique triangulation. The research results show that: 1) multireligious culture is understood as a system of values, beliefs, and social practices based on three layers of culture (basic assumptions, adopted values, and artifacts) that emphasize harmony and non-discrimination; 2) the character of tolerance is reflected thru six indicators: recognition of differences, mutual respect, freedom of belief, coexistence, self-control, and justice; 3) the contribution of multireligious culture to the development of the character of tolerance occurs systematically thru three layers of culture. First, artifacts in the form of symbols of love and joint activities among followers of different religions; second, the values upheld, namely mutual respect, harmony, and justice, are instilled thru vision & mission, regulations, and exemplary behavior; third, the underlying assumptions of the school community are the belief that diverse religions are a natural reality and the belief that human relationships are inclusive, egalitarian, and collaborative.